Von Willebrand factor targeted thrombolysis in canine basilar artery occlusion - Carfora, Arianna; Holthaus, Blake; Yacoub, Simon; Franceschelli, Dominic; Joseph, Matthew; Milks, Michael W.; Mandybur, Ian; Anderson, Cole; Lee, Catherine; Huttinger, Allyson; Shujaat, Mohammad; Wheeler, Debra G.; et al. (Frontiers in Neurology, 2024)
Background and Purpose: Posterior circulation strokes, accounting for 20% of acute ischemic strokes, significantly contribute to morbidity and mortality. Fibrinolysis by rtPA improves outcomes in stroke but the risk of intracranial hemorrhage limits benefit. Arterial recanalization of basilar artery occlusion by thrombolysis or endovascular thrombectomy improves outcomes in posterior circulation strokes. This study investigates a VWF-targeting RNA aptamer as a safer and more effective alternative to rtPA in a canine model.Autologous clots were placed into the basilar artery to induce stroke in 24 beagles. To compare reperfusion, 0.9 mg/kg rtPA, 0.5 mg/kg BB-031, or vehicle were administered 60 minutes after the initiation of occlusion. Digital subtraction angiography, laser speckle imaging and magnetic resonance imaging were used to assess recanalization, reperfusion and infarct volume respectively.Results: Treatment with BB-031 resulted in recanalization of the posterior circulation on digital subtraction angiography with no evidence of microembolism assessed at sacrifice. 66.5% of animals treated with BB-031 resulted in reperfusion with a TICI score of > 1 whereas vehicle remained at TICI score 0 as did all but one rtPA animal at sacrifice. Improved perfusion was seen in the basilar artery and surrounding blood vessels visualized through the cranial window with laser speckle imaging to 47% of its original baseline in BB-031 group compared to rtPA at 37% and vehicle at 22%. Finally, BB-031-treatment resulted in an approximate 32% mean infarct volume, significantly smaller on magnetic resonance imaging compared to 56% in vehicle treated and 48% with rtPA treatment.Targeted inhibition of VWF by BB-031 increased recanalization and reperfusion, and reduced infarct volume in a canine model of BAO stroke. It represents a promising target based on preliminary results for treating acute ischemic stroke.